The social unconscious : selected papers - Hopper, Earl. (London ; Philadelphia : J. Kingsley Publishers, 2003)
The social unconscious and its manifestations in group analysis are the focus of this important new book of Earl Hopper's selected papers. Drawing on sociology, psychoanalysis and group analysis, he argues that groups and their participants are constrained unconsciously by social, cultural and political facts and forces. These hypotheses are illustrated with clinical vignettes concerning anti-Semitism, racism, the politics of class and gender, and the effects of rapid social change. Transference and countertransference processes are examined both vividly and honestly. Theoretically generative.
7 Wounded Bird: A Study of the Social Unconscious and Countertransference in Group Analysis8 On the Nature of Hope in Psychoanalysis and Group Analysis1; SUBJECT INDEX; AUTHOR INDEX.
Includes bibliographical references and indexes.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Group psychotherapy; Psychoanalysis; Subconsciousness; Social psychology; Psychoanalysis; Unconscious, Psychology; Psychology, Social; Psychotherapy, Group -- methods; Psychotherapy, Group; Psychoanalytic Theory; Psychothérapie de groupe; Psychanalyse; Inconscient; Psychologie sociale; psychoanalysis; social psychology; unconscious; Social, Group Or Collective Psychology; Psychotherapy; PSYCHOLOGY -- Psychotherapy -- Group; Social psychology; Group psychotherapy; Psychoanalysis; Subconsciousness